Clinical Pharmacokinetics and Pharmacodynamics of the Endothelin Receptor Antagonist Macitentan - Sidharta, P. N.; Treiber, A.; Dingemanse, J. (Clinical pharmacokinetics, 2015)
Pulmonary arterial hypertension (PAH) is a progressive disease of the lung vascular system, which leads to right-sided heart failure and ultimately death if untreated. Treatments to regulate the pulmonary vascular pressure target the prostacyclin, nitric oxide, and endothelin (ET) pathways. Macitentan, an oral, once-daily, dual ET A and ET B receptor antagonist with high affinity and sustained receptor binding is the first ET receptor antagonist to show significant reduction of the risk of morbidity and mortality in PAH patients in a large-scale phase III study with a long-term outcome. Here we present a review of the available clinical pharmacokinetic, pharmacodynamic, pharmacokinetic/pharmacodynamic relationship, and drug–drug interaction data of macitentan in healthy subjects, patients with PAH, and in special populations.